Effect of Intrathecal Dexmedetomidine as Adjuvant to Hyperbaric Bupivacaine for Total Abdominal Hysterectomy: A Double Blind Control Study - Jabbar, Abdul; Begum, Kawsar; Laila, Rona; Sardar, Kawsar; Uddin, Raihan; Rahman, Mushfiqur; Begum, Muslema (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Aims and Objectives: The aim of this study is to evaluate the effects of Dexmedetomidine as intrathecaladjuvant to Bupivacaine in spinal anaesthesia on the onset and duration of sensory and motor block inTotal Abdominal Hysterectomy (TAH). Materials and Method: Sixty patients of ASA status I and II posted for Total Abdominal Hysterectomywere randomly divided into three groups. Group C were administered Hyperbaric Bupivacaine 15mgplus 0.5 ml normal saline, Group D was administered Hyperbaric Bupivacaine 15mg + Dexmedetomidine10mg in 0.5 ml normal saline. Duration and quality of sensory and motor block were assessed. Results: Sensory and motor block in group D patients were longer than group C patients. Conclusion: Intrathecal dexmedetomidine when added to bupivacaine heavy (0.5%) provide better andprolonged analgesia. JBSA 2019; 32(1): 18-23